Rewiring carotenoid biosynthesis in plants using a viral vector - Majer, Eszter; Llorente, Briardo; Rodríguez-Concepción, Manuel; Daròs, José-Antonio (Scientific reports, 2017)
Plants can be engineered to sustainably produce compounds of nutritional, industrial or pharmaceutical relevance. This is, however, a challenging task as extensive regulation of biosynthetic pathways often hampers major metabolic changes. Here we describe the use of a viral vector derived from Tobacco etch virus to express a whole heterologous metabolic pathway that produces the health-promoting carotenoid lycopene in tobacco tissues. The pathway consisted in three enzymes from the soil bacteria Pantoea ananatis . Lycopene is present at undetectable levels in chloroplasts of non-infected leaves. In tissues infected with the viral vector, however, lycopene comprised approximately 10% of the total carotenoid content. Our research further showed that plant viruses that express P. ananatis phytoene synthase (crtB), one of the three enzymes of the heterologous pathway, trigger an accumulation of endogenous carotenoids, which together with a reduction in chlorophylls eventually result in a bright yellow pigmentation of infected tissues in various host-virus combinations. So, besides illustrating the potential of viral vectors for engineering complex metabolic pathways, we also show a yellow carotenoid-based reporter that can be used to visually track infection dynamics of plant viruses either alone or in combination with other visual markers.